Prophetic Parenting Sebagai Paradigma Pendidikan Karakter - Yuslia Styawati (Sekolah TinggiAgama Islam Negeri (STAIN) Kediri, 2016)
Character education has become something that is extremely needed compared to previous decades. Moral damages in the form of delinquency, robbery, violence, bulliying, corruption, and bribery become common today. In this instance, modern culture is unable to gadually and comprehensively overcome these social pathologies, and even modern education makes these worse. Therefore, prophetic parenting is an evolutionary solution to change this serious condition with future vision, not an instant solution.